Aktivitas Antioksidan Fraksi Metanol Ekstrak Batang Merung (Coptosapelta tomentosa (Blume) Valenton ex K. Heyne) - Agustina Rahayu Magdaleni; Daniel Daniel (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2021)
Research of antioxidant activity of the merung stem (Coptosapelta tomentosa (Blume) Valenton ex K. Heyne) has been carried out. Extraction from the stem of the merung was carried out using solvents namely methanol, n-hexane and ethyl acetate. The results of the phytochemical test on crude extracts of the stem of the merung stem contains phenolic compounds, steroids and flavonoids. The methanol fraction contains phenolic compounds. Antioxidant activity test results with the addition of DPPH (1,1- diphenyl-2-picrylhidrazyl) showed in methanol fraction had an IC50 value of 163.25 ppm. The GC-MS analysis of the methanol fraction of merung stem contained compounds namely 4H-Pyran-4-one, 2,3-dihydro-3,5-dhydroxy-6-methyl (13.73). Keywords: Antioxidant Activity Test, Merung Stem, Phytochemical Test